The natural herbicide rhein targets photosystem I - Alyssa Twitty; Hamlin Barnes; Noa Levy; Yaniv Mizrahi; Yosef Geva; Yael Phillip; Franck E. Dayan (Scientific Reports)
Abstract The natural anthraquinone rhein has been identified as a novel herbicide with a potentially new mode of action using a generative AI system for functional molecules discovery. Its herbicidal activity was light-dependent and resulted in rapid burndown symptoms on leaves of treated plants. Rhein interferes with photosynthesis by acting as an electron diverter at the level of photosystem I (PSI). The redox potential of rhein suggests that it accepts electrons between P700 and NADP+ of PSI. This is consistent with the redox potential of rhein that enables it to accept electrons from flavoproteins. Ferredoxin-NAPD+ reductase is a flavoprotein with a redox potential near that of rhein. Thus, it is currently hypothesized that rhein acts as an electron acceptor at or near the PSI Ferredoxin-NAPD+ reductase to form a radical and generate reactive oxygen species that drive the light-dependent herbicidal effect which is observed in treated plants from greenhouse trials.